Chlamydia trachomatis Infection in Pregnancy: The Global Challenge of Preventing Adverse Pregnancy and Infant Outcomes in Sub-Saharan Africa and Asia - Adachi, Kristina (Biomed Res Int, 2016)
Screening and treatment of sexually transmitted infections (STIs) in pregnancy represents an overlooked opportunity to improve the health outcomes of women and infants worldwide. Although Chlamydia trachomatis is the most common treatable bacterial STI, few countries have routine pregnancy screening and treatment programs. We reviewed the current literature surrounding Chlamydia trachomatis in pregnancy, particularly focusing on countries in sub-Saharan Africa and Asia. We discuss possible chlamydial adverse pregnancy and infant health outcomes (miscarriage, stillbirth, ectopic pregnancy, preterm birth, neonatal conjunctivitis, neonatal pneumonia, and other potential effects including HIV perinatal transmission) and review studies of chlamydial screening and treatment in pregnancy, while simultaneously highlighting research from resource-limited countries in sub-Saharan Africa and Asia.